Desafios para a reforma das polícias no Brasil : reflexões à luz de experiências latino-americanas - Nelsis, Alícia Rösler (2021)
This work has as main objective to identify the possibilities to reform the Brazilian state police, seeking to insert this debate in the Latin American context, being divided into three parts. The first deals with the historical path of the police in Brazil, the debates on Public Security in the 1988 Assembleia Constituinte (Constituent Assembly), as well as the current design of the state police in the democratic period. The second part addresses the issue of police reforms in Latin America, in particular in Chile, Argentina and Colombia. In these cases, we seek to identify how the reform processes developed themselves and what were the main difficulties and improvements presented by these experiences. In the third part, it deals with police reforms conducted at the state level in Brazil, as well as analyzing the current stage of the debate on structural reforms based on the discussions held in the Câmara dos Deputados (House of Representatives). The main paths to conduct the theme in this House are then listed, notably the complete cycle of police and the unification of state police. Finally, this work reflects on the possibilities for the Brazilian case, drawing parallels with the cases examined in neighboring countries. The work, developed in the Postgraduate Program in Criminal Sciences of PUCRS, is part of the Criminal System and Violence concentration and in the line of research on Violence, Crime and Public Security.